Bayesian hierarchical species distribution modeling of blue catfish, an invasive species in tidal rivers of Virginia - Tang, Man; Jiao, Yan; Orth, Donald J. (Frontiers in Environmental Science, 2026)
Blue Catfish, an invasive species introduced into tidal waters of Virginia from the 1970s to mid-1980s, have rapidly expanded into many major tributaries in the Chesapeake Bay watershed. The increased abundance of Blue Catfish threatens the biodiversity of aquatic ecosystems through direct predation effects or indirectly by competition for limited resources with native species. To gain ecological insights and to predict the distributions along environmental gradients, four Bayesian species distribution models, were applied to estimate the abundance changes of the Blue Catfish by examining the relative influence of environmental and temporal factors on Blue Catfish catches from annual surveys in tidal rivers of Virginia. The analyses were based on sampling data collected from low- and high-frequency electrofishing surveys. The Bayesian hierarchical model was selected as the final model based on the deviance information criterion (DIC) value and a consideration of the underlying data structure. In this study, the presence and relative abundance of Blue Catfish were influenced by salinity and temperature. The detected density of Blue Catfish decreases when salinity and temperature increase in general. Standardized relative abundance among years was highly variable but increased over time in the low-frequency electrofishing survey. However, in the high-frequency electrofishing survey, this trend was not apparent. We recommend continued monitoring in these and other tidal rivers to provide management strategies that control the spread and limit the ecological impacts of Blue Catfish on native species. Our analysis also provides a standardized framework for evaluating invasive Blue Catfish distribution and relative abundance across multiple rivers.